Exercise interventions for pulmonary function impairment: rehabilitation strategies from the acute phase to long-term sequelae - Guo, Yunpeng; Huo, Lei; Zhang, Zhanyi (Frontiers in Physiology, 2025)
Pulmonary function impairment, as a major global public health concern, significantly affects respiratory function, quality of life and mortality. Its pathological features include impaired gas exchange, reduced exercise tolerance, and chronic inflammatory responses. Conventional non-pharmacological interventions, such as protective mechanical ventilation, prone positioning, and extracorporeal membrane oxygenation (ECMO), can improve oxygenation but are limited by risks of complications, poor patient tolerance, and high dependence on equipment. Pharmacological therapies may regulate inflammatory responses; however, their long-term application is constrained by safety concerns and interindividual variability in efficacy. The discussion of the benefits and mechanisms of exercise interventions includes an explanation of their applicability to patients across various types and stages of pulmonary function impairment. In addition, this study systematically elucidates the mechanisms and implementation strategies of exercise interventions across different stages of pulmonary impairment, including the acute phase, recovery phase, and long-term management phase. It further proposes a personalized exercise prescription framework based on biomarkers. The study emphasizes the development of dynamic adjustment systems and stratified management strategies tailored for special populations such as the elderly and children, thereby providing a theoretical foundation for optimizing pulmonary rehabilitation outcomes.